Analisis Agilitas Operasional dan Fleksibilitas Lokasi: Studi Kasus pada Model Bisnis Kopi Keliling Ini Kopi - Nanda Fitria Aulanda; Nur Fatiha Utami Nasution; Nina Annisa; Ikhwan Kurnia Hutasuhut (Indo Publishing, 2026)
The development of the modern coffee industry encourages business actors to adopt adaptive business models through enhanced operational agility and location flexibility. This study aims to analyze the integration of operational agility and location flexibility in the mobile coffee business model of Ini Kopi in supporting business performance stability and the creation of competitive advantage.This research employs a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, direct observation of the operations of four cart units, and documentation of daily sales data. The findings indicate that operational agility and location flexibility are two strategic factors that are mutually integrated in supporting the performance of the Ini Kopi mobile coffee business model. Through the ability to adjust product variant composition, daily production volume, and adaptive selection of operational locations, the mobile coffee business is able to effectively respond to dynamic market demand. Location flexibility functions as a dynamic capability that strengthens operational agility, enabling the business to reach diverse consumer segments without relying on a single fixed sales point. This study provides a conceptual contribution to the development of MSME research based on business mobility, as well as practical implications for the development of fast-service beverage business models.